(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In the present scenario, 600 oC and 1000 oC annealed synthetic quartz material were irradiated by beta doses. The thermoluminescence glow curves are recorded for treated sample under influence of optical bleaching temperature and cutoff duration of 290 oC preheat temperature. The thermal and optical sensitivity of higher temperature TL glow peaks are to be examined including their dose response. Under the influence of optical bleaching either at room temperature or 160 oC, the growth of 375 oC TL glow peak is observed at 600 oC annealed sample by complete bleaching of 350 oC glow peak. However, the thermal stability and optical sensitivity of this peak is increased when the temperature is increased to1000 oC annealed sample accordance with new 220 oC TL glow peak by complete optical bleaching of 300 oC glow peak. The cutoff durations of 290 oC preheat temperature followed optical bleaching at 160 oC show unique contribution of 375 oC and 220 oC glow peaks in 600 oC and 1000 oC annealed sample respectively. This Study focussed on the Thermal and Optical Sensitivity of Higher Thermo luminescence Glow Peaks in Synthetic Quartz Material. The changes in TL outcomes are elaborated by thermal and optical sensitization properties of TL traps under annealing treatment, pre-heat temperature and optical bleaching temperature.